GAMBARAN STATUS GIZI BAYI USIA 0-6 BULAN DI POSYANDU BOGENVIL PUSKESMAS OESAPA KOTA KUPANG - Andini Welmince Saba; Theresia Mindarsih; Maria Paula Marla Nahak (Universitas Citra Bangsa, 2020)
ABSTRACT Background. Infant nutritional status is a state of the body that is the result of food consumption and use of nutrients with 4 classifications, namely poor nutritional status, poor status, good nutritional status, more nutritional status. The quality of babies born is very dependent on the state of the mother before and during pregnancy. Aim. This study aims to describe the nutritional status of infants aged 0-6 months in Posyandu Bogenvil working at the Kupang Oesapa Community Health Center. Method. The research method used is descriptive using a survey research design conducted at the Bogenvil Posyandu 1 to 14 working area of the Kupang City Oesapa Health Center. Result. Based on the research, it was found that from 44 respondents, most respondents experienced good nutritional status of 22 respondents (50.0%). This research is expected to be an input for health workers and parents of infants in providing services in the form of education to mothers about the importance of good nutritional status during pregnancy and routine checks on infants to prevent nutritional problems in infants. Keywords: Nutrition, Nutritional status of infants, Nutritional problems